The mechanics of shallow magma reservoir outgassing. (8th August 2017) - Parmigiani, A.; Degruyter, W.; Leclaire, S.; Huber, C.; Bachmann, O.
Abstract: Magma degassing fundamentally controls the Earth's volatile cycles. The large amount of gas expelled into the atmosphere during volcanic eruptions (i.e., volcanic outgassing) is the most obvious display of magmatic volatile release. However, owing to the large intrusive:extrusive ratio, and considering the paucity of volatiles left in intrusive rocks after final solidification, volcanic outgassing likely constitutes only a small fraction of the overall mass of magmatic volatiles released to the Earth's surface. Therefore, as most magmas stall on their way to the surface, outgassing of uneruptible, crystal‐rich magma storage regions will play a dominant role in closing the balance of volatile element cycling between the mantle and the surface. We use a numerical approach to study the migration of a magmatic volatile phase (MVP) in crystal‐rich magma bodies ("mush zones") at the pore scale. Our results suggest that buoyancy‐driven outgassing is efficient over crystal volume fractions between 0.4 and 0.7 (for mm‐sized crystals). We parameterize our pore‐scale results for MVP migration in a thermomechanical magma reservoir model to study outgassing under dynamical conditions where cooling controls the evolution of the proportion of crystal, gas, and melt phases and to investigate the role of the reservoir size and the temperature‐dependent viscoelastic response of the crust on outgassing efficiency. We find that buoyancy‐driven outgassing allows for a maximum of 40–50% volatiles to leave the reservoir over the 0.4–0.7 crystal volume fractions, implying that a significant amount of outgassing must occur at high crystal content (>0.7) through veining and/or capillary fracturing. Key Points: Outgassing potential of a magma reservoir is a strong function of its crystal content Outgassing efficiency is also modulated by mechanical coupling between reservoir and crust Simulations that consider both aspects reveal that the majority of exsolved volatiles is released at intermediate to high crystallinity